Effect of Antihypertensives by Class on Cerebral Small Vessel Disease: A Post Hoc Analysis of SPRINT-MIND. Issue 8 (4th May 2022) - Goldstein, Eric D.; Wolcott, Zoe; Garg, Gauri; Navarro, Kayla; Delic, Alen; Yaghi, Shadi; Sederholm, Benson; Prabhakaran, Shyam; Wong, Ka-Ho; McLean, Kaitlin; de Havenon, Adam H.
Abstract : Background: Treatment of uncontrolled arterial hypertension reduces the risk of cerebral small vessel disease (CSVD) progression, although it is unclear whether this reduction occurs due to blood pressure control or class-specific pleiotropic effects, such as improved beat-to-beat arterial pressure variability with calcium channel blockers. The goal of this study was to investigate the influence of antihypertensive medication class, particularly with calcium channel blocker, on accumulation of white matter hyperintensities (WMH), a radiographic marker of CSVD, within a cohort with well-controlled hypertension. Methods: We completed an observational cohort analysis of the SPRINT-MIND trial (Systolic Blood Pressure Trial Memory and Cognition in Decreased Hypertension), a large randomized controlled trial of participants who completed a baseline and 4-year follow-up brain magnetic resonance image with volumetric WMH data. Antihypertensive medication data were recorded at follow-up visits between the magnetic resonance images. A percentage of follow-up time participants were prescribed each of the 11 classes of antihypertensive was then derived. Progression of CSVD was calculated as the difference in WMH volume between 2 scans and, to address skew, dichotomized into a top tertile of the distribution compared with the remaining. Results: Among 448 individuals, vascular risk profiles were similar across WMH progression subgroups except age (70.1±7.9 versus 65.7±7.3 years; P <0.001) and systolic blood pressure (128.3±11.0 versus 126.2±9.4 mm Hg; P =0.039). Seventy-two (48.3%) of the top tertile cohort and 177 (59.2%) of the remaining cohort were in the intensive blood pressure arm. Those within the top tertile of progression had a mean WMH progression of 4.7±4.3 mL compared with 0.13±1.0 mL ( P <0.001). Use of angiotensin-converting enzyme inhibitors (odds ratio, 0.36 [95% CI, 0.16–0.79]; P =0.011) and dihydropyridine calcium channel blockers (odds ratio, 0.39 [95% CI, 0.19–0.80]; P =0.011) was associated with less WMH progression, although dihydropyridine calcium channel blockers lost significance when WMH was treated as a continuous variable. Conclusions: Among participants of SPRINT-MIND trial, angiotensin-converting enzyme inhibitor was most consistently associated with less WMH progression independent of blood pressure control and age.